Is family time failing? : a study on Singapore youths’ perspectives towards family time in enhancing the quality of parents-youth relationship. - Lee, Joanna Hui Ling. (2009)
Studies conducted on Western families often emphasize the importance of family time in enhancing the relationship between parents and youths. Moreover, these studies tend to focus on the parents’ perspectives on family time and neglect the youths’ perspectives. This study seeks to explore the perspectives that Singapore youths have towards family time in enhancing the quality of the relationship with their parents. It proposes that there is a contradiction in the tools that youths use to talk about the importance of family time and the practice of family time. In practice,the time spent is for other utilitarian purposes and not designed for enhancing the quality of parents-youth relationship. The disjuncture in the ideology and practice of family time is due to the habitus that the youths possess. Therefore, youths do not recognize that family time is effective in enhancing the quality of parents-youth relationship.